PRINCIPLES OF ESTIMATING SOIL MOISTURE PARAMETERS IN THE BASIN - KHODAN, Halyna (Iași 2022, 2022)
In the vertical structure of the river basin, the dominant formation is the soil. Conditions for the transformation of water supply to the surface of the basin are determined by the ability of the soil to give or, contrarily, retain a significant proportion of precipitation.
Keywords: Infiltration, particle size distribution, soil moisture, porosity, filtration coefficient.